(untitled) (Research, Society and Development, 2023)
With the objective of analyzing the growth of two sorghum hybrids (BRS 800 and CMSXS 766), cultivated under different spacing between plants, in a grazing area in the north of Tocantins. The experimental design was in randomized blocks, in a 2x4 factorial arrangement, with two sorghum hybrids for grazing (BRS 800 and CMSXS 766), four spacings (15, 30, 45 and 60 cm) and four replications, totaling 32 experimental units. The two hybrids analyzed are the result of crossing grain sorghum (Sorghum bicolor (L.) Moench) with Sudan sorghum (Sorghum sudanense (Piper) Stapf) and are suitable for grazing. The evaluations consisted of: crop growth rate (TCC), leaf accumulation rate (TAcF), stem accumulation rate (TAcC), leaf-to-stem ratio (FC), leaf area ratio (RAF), weight ratio (RPF), and specific leaf area (AFE). As a result, the sorghum hybrid for grazing when planted in a dense way (800,000 thousand plants per hectare) increased productivity and CMSXS 766 was the most productive under the experimental conditions used. The sorghum hybrids BRS 800 and CMSXS 766 are viable in the State of Tocantins and can be used up to the third regrowth.